Occurrence, antimicrobial resistance and genomic features of Klebsiella pneumoniae from broiler chicken in Faisalabad, Pakistan - Khan, Muhammad Moman; Mushtaq, Muhammad Ahmed; Abbas, Nayyar; Fatima, Fariha; Gibbon, Marjorie J.; Schierack, Peter; Mohsin, Mashkoor (Frontiers in Veterinary Science, 2024)
The dissemination of antimicrobial resistance (AMR) in critical priority pathogens is a significant threat. Non-clinical reservoirs of AMR, such as agriculture and food production facilities, may contribute to the transmission of clinically relevant pathogens such as multidrug-resistant (MDR) Klebsiella pneumoniae. There is currently very limited knowledge regarding the population structure and genomic diversity of K. pneumoniae in poultry production in Pakistan. We explored healthy broilers in a commercial farm from Faisalabad, Pakistan, and identified six K. pneumoniae strains from 100 broiler birds. We characterized the strains, determining clonality, virulence and antimicrobial resistance genes using next generation sequencing. The evaluation of antimicrobial susceptibility revealed that all the strains were MDR. Genomic analysis showed that 3/6 strains belonged to ST152, harbouring acquired resistance aminoglycosides [aadA2, aph(4′)-Ia], β-lactams (blaSHV-187, blaLAP2), fosfomycin (fosA6), tetracycline (tetA), trimethoprim (dfrA12), quinolone (qnrS1), sulphonamides (sul2) and phenicol (floR). All the strains harboured the efflux pump genes oqxA, oqxB, emrR, kpnG, kpnH, kpnF, baeR, mtdB and mtdC. All six strains encoded identical virulence profiles possessing six genes i.e., ureA, iutA, entB, allS, fimH and mrkD. Phylogenomic analysis of the dominant sequence type (ST152) present in our dataset with publicly available genomes showed that the isolates clustered to strains mainly from human sources and could pose a potential threat to food safety and public health. The combination of these findings with antimicrobial use data would allow a better understanding of the selective pressures that may be driving the spread of AMR. This is the first report of MDR K. pneumoniae isolated from broiler hens in Pakistan, and the finding suggests that routine surveillance of WHO critical priority pathogens in such settings would be beneficial to the development of effective control strategies to reduce AMR.